Impact of Serum Prolactin and Testosterone Levels on the Clinical Parameters of Dry Eye in Pregnant Women - Samuel Kyei; Richard K. Dadzie Ephraim; Stephen Animful; Madison Adanusa; Stephen Karim Ali-Baya; Belinda Akorsah; Mabel Antwiwaa Sekyere; Kofi Asiedu (Journal of Ophthalmology)
Purpose. To explore the relationship between serum prolactin, testosterone level, and tear film parameters. The potential impact of these hormones on the health of the ocular surface in pregnant women was evaluated. Methods. This was a hospital-based cross-sectional study in which ocular symptoms (Ocular Surface Disease Index (OSDI)), tear function (fluorescein tear breakup time, Schirmer’s test 1), corneal and conjunctival staining, meibomian gland (MG) expressibility, and quality of secretion were measured. Lid margin findings including lid notching, thickness, and lid margin telangiectasia were also recorded. Venous blood was collected and the serum concentrations of prolactin and testosterone were determined using ELISA kits. Correlation and multiple linear regression analyses were used to examine predictors of dry eye symptoms and signs. Results. A total of 160 pregnant women participated in the study and their mean age was 30.1 ± 4.6 years (range 18–42 years). The correlation analysis indicated that testosterone concentration did not significantly correlate with any of the clinical parameters hence it was not included in the linear regression analysis. However, prolactin serum concentration correlated significantly with Schirmer’s test 1. Multiple linear regression was done to predict participants’ Schirmer’s test 1 score based upon their ocular surface staining score (oxford grading scale), meibomian gland expressibility, meibomian secretion quality, and serum concentration of prolactin. Only predictors that significantly correlated with Schirmer’s test 1 in the correlation analysis were included in the linear regression analysis. A significant regression equation was obtained (F (2, 157) = 5.119, p=0.007) with an R square of 0.05. Multiple linear regression analysis revealed that concentration of prolactin (ß coefficient = 0.032, p=0.044) and meibomian gland expressibility scores (ß coefficient = 2.14, p=0.016) were associated with Schirmer’s test 1 scores when adjusted for duration of pregnancy. Conclusion. The study showed that increased serum prolactin levels have a weak but positive impact on Schirmer’s test 1 scores whilst serum testosterone level has no association with the clinical parameters of dry eye in pregnant women.